Dissertações e teses da enfermagem brasileira acerca da unidade de terapia intensiva - Maria Angélica Bezerra dos Santos; Guilherme Guarino de Moura Sá; Joselany Áfio Caetano; Alana Bartolo da Costa; Marcela Lourene Correia Muniz; Nelson Miguel Galindo (Universidade Federal do Ceará, 2017)
Objective: to analyze the Brazilian scientific production of nursing dissertations and theses conducted in Adult Intensive Care Unit. Methods: a bibliometric study through electronic access to the Center for Nursing Studies and Research of the Brazilian Nursing Association was carried out, collecting a sample of 123 dissertations and 27 theses. Results: there was an increase in the number of studies over the years; 54.6% were conducted the Southeast and 26.0% from the South regions of the country. As for the type of study, 70.0% were descriptive and 59.3% quantitative. Regarding the theme most frequently researched, 43.3% addressed nursing care, and 38.0% had critical patients as the target population of the scientific research. Conclusion: brazilian nursing theses and dissertations conducted in Adult Intensive Care Unit were predominantly made up of descriptive and quantitative studies carried out in the Southeast and South regions, and addressing the nursing care provided to patients.